2019
DOI: 10.25271/sjuoz.2019.7.4.647
|View full text |Cite
|
Sign up to set email alerts
|

New Data Hiding Approach Based on Biological Functionality of DNA Sequence

Abstract: Data hiding or steganography has been used ever since a secret message was needed to be transferred. Data hiding methods need a medium to be cover for secret message that is to be sent. Different mediums are used such as image, video, audio, and last decade the deoxyribose nucleic acid (DNA). In this paper, a new data hiding approach based on the DNA sequence is proposed. Unlike many existing methods, the proposed method does not change the biological functionality of the DNA reference sequence when the sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…The cracking probabilities of the proposed technique and several other techniques discussed in the literature review, including Malathi et al (2017) , Sajisha & Mathew (2017) , Agrawal, Srivastava & Sharma (2014) , Marwan, Shawish & Nagaty (2015) , Abdullah, Eesa & Abdo (2019) , are presented in Table 4 . The proposed technique demonstrated the lowest cracking probability among these techniques, indicating a higher level of security.…”
Section: Discussionmentioning
confidence: 99%
“…The cracking probabilities of the proposed technique and several other techniques discussed in the literature review, including Malathi et al (2017) , Sajisha & Mathew (2017) , Agrawal, Srivastava & Sharma (2014) , Marwan, Shawish & Nagaty (2015) , Abdullah, Eesa & Abdo (2019) , are presented in Table 4 . The proposed technique demonstrated the lowest cracking probability among these techniques, indicating a higher level of security.…”
Section: Discussionmentioning
confidence: 99%
“…The cracking probabilities of the proposed technique and the techniques [15], [4], [42], [48] and [49] that were discussed in the literature review are shown in Table 3. The proposed technique achieved the lowest cracking probability compared to other techniques.…”
Section: Cracking Probabilitymentioning
confidence: 99%